Effects of omega-3 fatty acid supplementation on the risk of atrial fibrillation (AF) and micro-AF in the OMEMI trial. (3rd October 2022) - Myhre, P; Berge, T; Kalstad, A; Tveit, S H; Laake, K; Schmidt, E B; Solheim, S; Arnesen, H; Seljeflot, I; Tveit, A
Abstract: Background: Findings from recent clinical outcome trials have raised concerns regarding potential off target adverse effects from supplementation with n-3 polyunsaturated fatty acids (PUFA) on atrial fibrillation (AF) risk. Purpose: We aimed to assess AF and "micro-AF" in elderly patients with myocardial infarction (MI), randomized to n-3 PUFA or placebo. Methods: In the OMEMI trial, 70–82 years old patients with a recent MI were randomized to 1.8g/day of eicosapentaenoic/docosahexaenoic acid (EPA/DHA) or placebo (corn oil) for two years. New-onset AF was recorded by clinical detection and by screening, also for "micro-AF" (episodes of ≥3 consecutive irregular supraventricular ectopic beats), by two weeks Zenicor thumb ECG (adjudicated by investigators blinded to treatment allocation). Serum phospholipid content of EPA and DHA was determined by gas chromatography at baseline and study end. Results: Of 1014 patients in the OMEMI trial, 759 (75%) had no history of AF at baseline. These patients were aged 75±4 years and 542 (71%) were male. During the two year follow-up 43 patients developed new-onset AF (39 clinically-detected and 4 by thumb-ECG screening). In addition, 27 patients had episodes of micro-AF, yielding a total of 70 patients with new-onset AF or micro-AF. In the n-3 PUFA group 46 (11.9%) had AF/micro-AF (28 AF and 18 micro-AF) while in the placebo group 24 (6.5%) had AF/micro-AF (15 AF and 9 micro-AF); HR 1.90 (95% CI 1.16–3.11, P=0.011; Figure 1, panel A). In both treatment arms combined, EPA increased with a mean of 60% in no-AF, 80% in micro-AF and 110% in AF (P=0.003 for linear trend; Figure 1, panel B). In patients randomized to n-3 PUFA, EPA increased with a mean of 120% in no-AF, 130% in micro-AF and 180% in clinical-AF (P=0.04 for linear trend). There were no significant associations between changes in DHA and new-onset AF. Conclusion: Supplementation with 1.8 g of n-3 PUFA to post MI patients increased the risk of micro-AF and AF, and there seemed to be a graded association between increases in serum EPA and the risk of micro-AF and AF. Changes in serum DHA was not related to the risk of AF/micro-AF. Funding Acknowledgement: Type of funding sources: None.